(untitled) (Veterinary Science, 2017)
The resistance of different pathogens to antimicrobials is a complication present in clinical practice in human and veterinary medicine. The incidence of Staphylococcus aureus resistant to methicillin in animals and its transmission to other hosts is especially considered because it has been present as a growing problem in the last decade. The ability of Staphylococcus aureus to develop resistance mechanisms makes necessary to know its epidemiology as a contribution to establish reasonable measures of prevention and control. The knowledge of the bases of resistance to beta-lactam antibiotics, the incidence in man of infections caused by Staphylococcus aureus resistant to methicillin in hospitals and in the community, and the possible therapeutic options are described in this article